2023
DOI: 10.1021/jacs.3c00565
|View full text |Cite
|
Sign up to set email alerts
|

Dopant- and Surfactant-Tuned Electrode–Electrolyte Interface Enabling Efficient Alkynol Semi-Hydrogenation

Abstract: Electrochemical alkynol semi-hydrogenation has emerged as a sustainable and environmentally benign route for the production of high-value alkenols, featuring water as the hydrogen source instead of H2. It is highly challenging to design the electrode–electrolyte interface with efficient electrocatalysts and their matched electrolytes to break the selectivity-activity stereotype. Here, boron-doped Pd catalysts (PdB) and surfactant-modified interface are proposed to enable the simultaneous increase in alkenol se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 55 publications
0
49
0
1
Order By: Relevance
“…Selective semihydrogenation of alkynes provides an important way to access fine chemicals and useful building blocks. , Typically, reducing the adsorption of alkene on the electrocatalyst surface and elevating the energy barrier of alkene over hydrogenation are two key aspects to ensuring a high alkene selectivity (Figure a). In these regards, the factors of good affinity to alkynes, excellent properties of hydrogen storage, and phosphorus (P)-modified nanomaterials demonstrating high activity toward HER , make P-modified Pd a potential candidate.…”
Section: Electrocatalytic Hydrogenation Of Organics With H2o Over Nan...mentioning
confidence: 99%
“…Selective semihydrogenation of alkynes provides an important way to access fine chemicals and useful building blocks. , Typically, reducing the adsorption of alkene on the electrocatalyst surface and elevating the energy barrier of alkene over hydrogenation are two key aspects to ensuring a high alkene selectivity (Figure a). In these regards, the factors of good affinity to alkynes, excellent properties of hydrogen storage, and phosphorus (P)-modified nanomaterials demonstrating high activity toward HER , make P-modified Pd a potential candidate.…”
Section: Electrocatalytic Hydrogenation Of Organics With H2o Over Nan...mentioning
confidence: 99%
“…Selective hydrogenation of acetylene is a cost‐effective method to prepare polymer‐grade ethylene on a large scale [5,6] . Recently, researchers have found that utilizing water as a proton source and renewable electric energy makes it possible to selectively transform one‐carbon molecules and unsaturated hydrocarbons at standard temperature and pressure [7–10] . The electrochemical acetylene semihydrogenation process has been verified to be an alternative to the traditional thermal catalytic hydrogenation process [11–14] .…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39] Dimethyl sulfoxide (DMSO), as a highly polar aprotic solvent, can modulate the hydrogen-bond environment of water, reducing the water dissociation activity and suppressing the hydrogen evolution reaction (HER). [3,29,31,40,41] It can be postulated that hydrogen-bond interactions between DMSO and water can alter the proton transfer ability of the PCET process, thus modulating the activity and selectivity of ORR.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of the hydrogen‐bond network at the electrode‐electrolyte interface strongly affects the transport of water molecules from the bulk electrolyte to the interface, which is crucial for the formation and utilization of active H* species from water dissociation [37–39] . Dimethyl sulfoxide (DMSO), as a highly polar aprotic solvent, can modulate the hydrogen‐bond environment of water, reducing the water dissociation activity and suppressing the hydrogen evolution reaction (HER) [3, 29, 31, 40, 41] . It can be postulated that hydrogen‐bond interactions between DMSO and water can alter the proton transfer ability of the PCET process, thus modulating the activity and selectivity of ORR.…”
Section: Introductionmentioning
confidence: 99%